Aeroelastic analysis of an idealized landing gear door in subsonic potential flow. (November 2020) - Morris, Benjamin K.; Davis, R. Benjamin
Abstract: Landing gear doors on aircraft have experienced flutter during preliminary flight testing. While designs vary widely, landing gear doors are typically plate-like structures with a relatively rigid actuator attached to their inside surface. To better understand the aeroelasticity of landing gear doors, this study investigates the aeroelastic stability of an idealized model. The model consists of a hinged plate with an interior constraint approximating the actuator attachment. The plate is subject to uniform flow, and an unsteady vortex lattice model is coupled to the structural model to predict critical flow velocities. The location and footprint area of the internal constraint, along with plate aspect and mass ratios, are varied to investigate a large parameter space. Results reveal that the critical flow speed and instability mechanism are sensitive to the postulated actuator placement. In general, flutter is the dominant mode of instability when the actuator is postulated in the leading quarter of the plate. In other postulated locations, divergence dominates. However, the exact shape and location of the boundary between flutter and divergence is configuration dependent and found to be especially sensitive to changes in aspect ratio.